STUDENTS’ PARTICIPATION IN RELIGIOUS EXTRACURRICULAR ACTIVITIES: THE RELATIONSHIP BETWEEN RELIGIOUS EXTRACURRICULAR ACTIVITIES AND ACADEMIC ACHIEVEMENT - Ayu Puji Rahayu; Deden Hilmansyah; Nizar Falilah; Kodar Rohmat; 5Mukhtiar Hussain Ibupoto (Raudhah - Proud To Be Professional, 2024)
Religious extracurricular activities are those conducted outside the core curriculum in the field of religion, such as the habit of praying in congregation, zakat practices, qurban practices, muhadoroh, religious studies, and similar activities. This study aimed to determine the relationship between student participation in religious extracurricular activities and academic achievement in the local content subject of worship practices. This study employs the ex post facto method. The data collection technique used in this study involved documentation provided by the school. Data were collected from records of final semester grades in religious extracurricular activities and student academic achievement in the local content subject of worship practices. The inferential statistical method used was the Pearson product-moment correlation test to analyze whether there was a significant relationship between the independent and dependent variables. The results showed that student participation in religious extracurricular activities had a significant relationship with academic achievement in the local content of worship practices. This is evidenced by the correlation test results, where the Sig (2-tailed) value of 0.000 is smaller than the α value of 0.05, indicating a significant relationship between variable X and variable Y. Keywords: Religious extracurricular activities, Academic achievement, Local content of worship practices